Réponses

2013-03-30T12:57:53+01:00
(4x+7)(2x-3)+(5x+2)(5x-2)=8x^2-12x+14x-21+25x^2-10x+10x-4=33x^2+2x-25

(5x-7)^2-(2x+3)(5x-7)=25x^2-35x-35x+49-(10x^2-14x+15x-21)=25x^2-70x+49-10x^2+14x-15x+21=15x^2-71x+70
2013-03-30T12:58:51+01:00
Dsl pour le gros pâté je suis sur tel. Développer : (4x + 7) (2x - 3) + (5x + 2) (5x - 2) = (8x au carré - 12x + 14x - 21) + (25x au carré - 4) = (8x au carré + 2x - 21) (25x au carré -4). Développer et réduire : (5x - 7)au carre - (2x + 3) (5x - 7) = (25x aucarré - 35x + 49) - (10x au carré - 14x + 15x - 21) = 25x au carré - 35x + 49 - 10x au carré - x + 21) = 15x au carré - 36x + 70.